ANALISIS KERUSAKAN LANDAS PACU BANDAR UDARA DENGAN METODE PCI DAN PERBAIKANNYA - Lahun Wahidah; Retno Ligina Ayu; Eko Wiyono (Construction and Material Journal, 2021)
One method aimed to know the condition of the pavement runway on an airport is pavement condition index (PCI). This method has three parameters, type damage, severity damage, and the number of damage or density. In this research, the assessment of PCI is done on a runway (flexible pavement) at one of the airports in Jakarta with a broad 3000 m x 45 m. PCI’s value is gained by following a method from ASTM D 5340-98 (Standard Test Method for The Airport Pavement Condition Index Surveys) from all total sample. The research obtained shows that runway airports have an average of 75,59 (very good). Consisting of excellent as many as 138 sample (38 %), very good as many as 102 sample (28 %), good 60 sample (17 %), fair 36 sample (10 %), poor 16 sample (5 %), very poor as many as 7 sample (2 %), and failed 1 sample (0.001 %). All repairs to the damaged area which are lower than excellent condition using patching with a cold milling machine.